Tecnologia social: contribuições educativas na perspectiva da comunidade de Mazagão Velho para preservação de saberes - (:unkn) unknown (Brasil)
This study discussed Social Technology: educational contributions from the perspective of the community of Mazagão Velho for the preservation of knowledge. The problematic question: How can Social Technology contribute to the process of preservation of traditional knowledge that is practiced during flour manufacturing, from the traditional African matrix community District of Mazagão Velho? The general objective is to contribute to families of the District of Mazagão Velho in the construction of educational possibilities based on the principles and meanings of Social Technology for the preservation of traditional knowledge practiced in the process of manufacturing cassava flour. The specific objectives of this study are to survey the families about the traditional knowledge and practices present in the flour subsistence activity; to discuss with the group the difficulties that lead to the loss of knowledge related to flour production; engaging families in dialogue meetings to build solutions for the preservation of their knowledge based on the concepts and meanings of Social Technology. The research was carried out in the Traditional Community of African Matrix District of Mazagão Velho, state of Amapá, with four oldest families who still practice traditional knowledge linked to subsistence flour making activity, and is based on the bases of the dialectical methodological framework, in the perspective of the qualitative approach, allied to the Culture Circle strategy. The theoretical references began with the understanding of the scholars as of Dagnino (2004, 2010, 2014); Diegues (2000, 2008); Freire (1999, 2013, 2015); Geertz (2008, 2012); Leff (2009) and Santos (2007, 2010), among others. Data analysis was based on Paulo Freire's Theory of Dialogical Action. The methodological course was divided into four phases, in the first one we performed a survey on the reality, using a questionnaire and semi-structured interview; the second was the choice of topics for discussion; already in the third, after listing the critical points with the group, we take to problematization; in the fourth phase we systematized the contributions of families. As results we present the contributions of the researched subjects, which were systematized from the testimonies collected during the encounters that occurred in the community. From this participatory process, a reflection scheme was generated that began in and for the community, proving that the principles of Social Technology are adequate and necessary for the preservation of traditional knowledge
Keywords: Tecnologia social; Educação; Saberes tradicionais; CNPQ::CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; EDUCAÇÃO, CULTURAS E DIVERSIDADES; EDUCAÇÃO, POLÍTICAS E CULTURAS